Morphological variation in the Brazilian Radiated Swamp Turtle Acanthochelys radiolata (Mikan, 1820) (Testudines: Chelidae) - Garbin, Rafaella C.; Karlguth, Deborah T.; Fernandes, Daniel S.; Pinto, Roberta R. (Zootaxa, 2016)
The freshwater turtle Acanthochelys radiolata (Mikan, 1820) is endemic to the Atlantic Forest domain in Brazil and few studies have been done on the morphology, geographic variation and taxonomy of this species. In this paper we record the morphological variation, as well as sexual dimorphism and ontogenetic changes in A. radiolata throughout its distribution range. We analyzed 118 morphological characters from 41 specimens, both quantitative and qualitative, and performed statistical analyses to evaluate size and shape variation within our sample. Morphological analysis revealed that A. radiolata is a polymorphic species, especially regarding color and shape. Two color patterns were recognized for the carapace and three for the plastron. Diagnostic characteristics of the species, such as the rounded tubercles on the neck and the shallow dorsal sulcus between the 2nd and 4th vertebral scutes, varied considerably. Acanthochelys radiolata also showed a high level of ontogenetic variation characterized by a change on the color pattern of plastron and limbs starting from the 4th month of life. Sexual size dimorphism was observed for the first time on nine morphometric variables and females showed larger sizes than males. Based on these results we conclude that A. radiolata represents one single polymorphic species distributed in the lowlands of the Brazilian Atlantic Forest from the state of Alagoas to the state of Rio de Janeiro and the south of Minas Gerais state.